Respostas fisiológicas do pintado (Pseudoplatystoma corruscans) a estressores comuns na piscicultura - Fagundes, Michele [UNESP] (2005)
The development of the aquaculture in Brazil has raised the interest for farming species with economic value such as the pintado, intensifying the rearing routine that might cause stress in fish when imposed in a inappropriate way. The present work evaluated the physiological responses of pintado (Pseudoplatystoma corruscans) exposed to handling procedures such as capture, transport and light. The study was divided in 3 experiments. In Experiment 1, 42 fish were submitted to capture (chasing and air exposure for 3 minutes) and sampled 5, 30, 60 minutes and 24 e 48 hours after estressor. In Experiment 2, 42 fish were transported for 12 hours in a closed system and sampled at arrival, 24 and 48 hours after. In Experiment 3, 26 fish were exposed to constant light (60w) or darkness for 24 hours. After that they were kept in the regular light regime (12 hours light and 12 hours darkness). In Experiment 1, cortisol levels were higher 30 minutes after the stressor and recovered the basal levels within 60 minutes; blood glucose levels increased from capture until 30 minutes after at levels that were kept for 24 hours; plasma chloride and osmolarity reduced slightly and hematocrit, red cell number and hemoglobin reduced suggesting hemodilution. In Experiment 2, plasma cortisol and blood glucose levels decreased 12 hours after transport and in Experiment 3 no significant difference was observed in cortisol e glucose levels after exposure to light or darkness, despite of the increase in hematocrit and red cell number in fish light exposed. The physiological responses of stress in pintado suggested the activation of the feedback mechanism in the cortisol secretion in long-term condition of stress and metabolic preference for fuel substrates other than glucose to supply the metabolic costs from homeostasis disturbance